Exergo-economic analysis of a batch chemical plant - Abdul Manan, Zainuddin; Hashim, Haslenda; Mansor, Shuhaimi (Penerbit UTM Press, 2000)
Exergy Analysis, also known as Thermodynamic Analysis, is a tool that has been widely used to analyse the energy efficient of continuous processes. It is a powerful analysis tool that is based on the First and the Second Law of Thermodynamics but has a least two shortcomings related to process environment. First, it provides a measure of process efficiency based on thermodynamics but does not point to ways to improve a process. Second, some results generated from an exergy analysis study may contradict economy. Both issues are addressed in this study. We introduce the term exergo-economic analysis to refer to the application of exergy analysis in conjunction with economic analysis. We apply exergo- economic analysis on a batch activated carbon plant to provide a complete guideline for process improvement. Calculations of the exergetic efficiencies along with the appropriate interpretations of the performance based on the First and Second Law of Thermodynamics lead to a number of desirable parametric and design changes for the process. By means of exergo-economic analysis, we show that a modification case involving a decrease in the exergetic efficiency may actually be economically desirable. Thus, we emphasize that economy must be made a key consideration in any exergy analysis study.